Administrative Behavior of the School administrators Under the Office of Chumphon Primary Education Area 1 - Thippahal, Sunansinee; Wijitwanna, Somtawin (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This research aimed to study and compare teachers' opinions on the administrative behaviors of the school administrators under Chumphon primary educational service area office 1. The sample consisted of 312 teachers in Chumphon primary educational service area office 1 in the academic year 2020 by using stratified random sampling according to the school size. The research instrument was a questionnaire. The data were statistically analyzed by using percentage, mean, standard deviation, t-test, One-Way ANOVA, and LSD. The research results were as follows: 1) Opinions of teachers on the administrative behaviors of the school administrators were at a high level in overall and particular aspects. The order from highest to lowest was as follows: the motivation, the goal, the communication, the decision-making, and the leadership, and 2) Comparison of teachers' opinions on the administrative behaviors of the school administrators under Chumphon primary educational service area office 1, classified by a) educational level: it did not have a difference in overall, but only the decision-making aspect had a statistically significant at a level of .01, b) work experience: it had a difference in overall and almost aspects, except for the motivation aspect and decision-making had no difference, and c) school size: it had a difference in overall and almost aspects, except for the motivation aspect and leadership had no difference.